2004
DOI: 10.1002/ijc.11718
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the MLH1, MSH2 and MSH6 genes in patients with double primary cancers of the colorectum and the endometrium: A population‐based study in northern Sweden

Abstract: Hereditary nonpolyposis colorectal cancer (HNPCC) is an autosomal dominant disorder that predisposes to predominantly colorectal and endometrial cancers due to germline mutations in DNA mismatch repair genes, mainly MLH1, MSH2 and in families with excess endometrial cancer also MSH6. In this population-based study, we analysed the mutation spectrum of the MLH1, MSH2 and MSH6 genes in a cohort of patients with microsatellite unstable double primary tumours of the colorectum and the endometrium by PCR, DHPLC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Indeed, Tanyi et al reported an HNPCC family with a truncating mutation in MSH2, which when in combination with MSH2 N127S leads to HNPCC phenotype in very early age. 17 Although the majority of the published data discusses MSH2 G322D as a neutral polymorphism, 3,5,[7][8][9][10][11][12] it has also been hypothesized to be a low penetrance allele. 24 This interpretation was supported by the functional analyses conducted with yeast assays, where the putative homologous mutation Msh2 D317D in yeast was reported to cause a moderate, as yet not complete inactivation of MMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Tanyi et al reported an HNPCC family with a truncating mutation in MSH2, which when in combination with MSH2 N127S leads to HNPCC phenotype in very early age. 17 Although the majority of the published data discusses MSH2 G322D as a neutral polymorphism, 3,5,[7][8][9][10][11][12] it has also been hypothesized to be a low penetrance allele. 24 This interpretation was supported by the functional analyses conducted with yeast assays, where the putative homologous mutation Msh2 D317D in yeast was reported to cause a moderate, as yet not complete inactivation of MMR.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested to be polymorphic when it was not segregating with the cancer phenotype in a family or it was found in healthy control individuals. 3,5,[7][8][9][10][11][12] Contrary to these, it was interpreted as a low penetrance allele based on moderate inactivation of yeast MMR caused by a homologous yeast variant. 13,14 It was also interpreted as pathogenic when it was segregating with the cancer phenotype, and showed loss of MSH2 protein and high microsatellite instability (MSI) in the tumor, 15 or when it was not found in healthy control chromosomes.…”
mentioning
confidence: 99%
“…Endometrial cancers occur with increased rates in women with hereditary nonpolyposis colorectal cancer (HNPCC), an autosomal dominant disorder that is linked to germ line mutations in one or more of the mismatch repair (MMR) genes including MLH1, MSH2 and MSH6 [1]. A direct consequence of DNA repair deficiency is the accumulation of DNA replication errors, or mutator phenotype, represented by high frequency of microsatellite instability (MSI-H).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and epidemiological studies have highlighted key genetic factors in human endometrial tumorigenesis, including loss or epigenetic silencing of the tumor suppressor gene phosphatase and tensin homologue (PTEN) 1 and the DNA mismatch repair (MMR) genes mutL homologue 1 (MLH1), mutS homologue 2 (MSH2) and mutS homologue 6 (MSH6). [2][3][4][5] It is widely accepted that exposure to unopposed estrogen (estrogen in the absence of progesterone) is a potent environmental risk factor for the development of a variety of malignancies, and in particular endometrial carcinoma. [6][7][8] However, deciphering the genes and pathways that are disturbed in estrogen-promoted endometrial cancers has been a difficult task, due in part to the inherent genetic and hormonal heterogeneity that characterizes this tumor type.…”
mentioning
confidence: 99%